Adhesive tape
By using a combination of thermally expandable microspheres composed of resin with carboxyl structural units in the adhesive tape and a specific adhesive, the floating and disengagement problems of the adhesive layer during heat stripping are solved, and efficient bonding and Peeling effect.
Patent Information
- Application Number
- CN202080055322.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-14
- Filing Date
- 2020-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-07-28
AI Technical Summary
When the conventional adhesive tape is heated and peeled off, the adhesive layer is prone to float and detachment, resulting in the problem of lowering adhesive force and residual adherence.
The thermally expandable microspheres composed of resin with carboxyl structural units are combined with an acrylic adhesive and an isocyanate crosslinking agent to form an adhesive tape expands at high temperature, causing concave and convexity on the surface of the adhesive layer to reduce adhesion. And improve the peeling property by the elastic layer and the separator.
Effectively prevent the adhesive layer from floating and detaching during heat peeling, maintain good adhesion and peelability, and reduce the residue of adhered.
Smart Images

Figure CN114174453B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive tape and more particularly to an adhesive tape capable of being easily releasable in response to a thermal stimulus. Background Art
[0002] As the adhesive tape used for the purpose of temporarily fixing the processed product in the process of manufacturing electronic components, it is known that the adhesive tape that shows adhesiveness when temporarily fixing and shows peelability when not needing to be fixed is easy to peel. As one of this adhesive tape, the adhesive tape (such as patent documentation 1) that has a base material and an adhesive layer and the adhesive layer contains the heat-expandable microspheres represented by an adhesive and a foaming agent and constitutes has been studied. This adhesive tape shows the desired adhesive force at a relatively low temperature represented at room temperature, and on the other hand, when heated to more than a specified temperature (foaming temperature), the foaming agent expands, produces concavo-convex on the adhesive layer surface, and the adhesive force reduces, that is, it can be heated and peeled. For this adhesive tape, only the effect of gravity can also be used to peel off the adherend.
[0003] The adhesive tapes described above have the problem that the adhesive layer sometimes floats from the substrate and then detaches depending on the situation. This is believed to be because when the deformation of the adhesive layer becomes larger, the substrate cannot be used to restrict the movement of the adhesive layer. The higher the temperature, the lower the elastic modulus of the adhesive layer, and the larger the deformation of the adhesive layer becomes. Therefore, the floating / detachment of the adhesive layer during heat peeling becomes a problem.
[0004] The adhesive tape as described above can be used as a temporary fixing tape in a heat treatment process (e.g., a heating process, a curing process, etc.). The foaming temperature of the temporary fixing adhesive tape in the heating process is set to be higher than the process temperature. In recent years, in order to improve the production takt of the heat treatment process, the heat treatment temperature of this process tends to be higher. Therefore, the foaming temperature of the adhesive tape is set to be higher, and as a result, the adhesive layer is prone to float / detach during heat peeling.
[0005] As the method for the floating / detachment of the adhesive layer when preventing the thermal stripping, can list: the method for setting the primer between substrate and the adhesive layer, the method for suppressing the deformation of the adhesive layer using high cross-linked adhesive, the method for reducing the content of heat-expandable microspheres etc. However, the limited effect realized by the method for setting the primer between substrate and the adhesive layer, because of the kind of adhesive, there is selectivity, therefore, is not a fundamental solution. In addition, in the method for suppressing the deformation of the adhesive layer using high cross-linked adhesive, there is the problem that the adherend retentivity is reduced because of the initial adhesion, and, in the method for reducing the content of heat-expandable microspheres, there is the problem of suppressing the thermal stripping property.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2001-131507 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The present invention has been made to solve the above-mentioned conventional problems, and an object of the present invention is to provide a pressure-sensitive adhesive tape that prevents a pressure-sensitive adhesive layer from floating off a substrate.
[0011] Solutions for solving problems
[0012] The adhesive tape of the present invention comprises a substrate and an adhesive layer disposed on at least one side of the substrate, the adhesive layer comprising heat-expandable microspheres and an adhesive, the heat-expandable microspheres comprising a shell and a volatile substance contained in the shell, and the resin constituting the shell comprises a structural unit having a carboxyl group.
[0013] In one embodiment, the glass transition temperature (Tg) of the resin constituting the shell is 120° C. or higher.
[0014] In one embodiment, the content ratio of the structural unit having a carboxyl group is 5 parts by weight to 97 parts by weight based on 100 parts by weight of the resin.
[0015] In one embodiment, the volatile substance is an organic solvent, and the difference (Tg-bp) between the boiling point (bp) of the organic solvent and the glass transition temperature (Tg) of the resin constituting the shell is 0° C. or more.
[0016] In one embodiment, the adhesive is an acrylic adhesive.
[0017] In one embodiment, the adhesive material includes an isocyanate crosslinking agent or an epoxy crosslinking agent.
[0018] In one embodiment, at an ambient temperature of 25° C., when the adhesive surface of the adhesive tape is attached to a polyethylene terephthalate film, the initial adhesive force a is 1.5 N / 20 mm to 20 N / 20 mm.
[0019] In one embodiment, the adhesive force b when the adhesive surface of the adhesive tape heated to 130°C and then cooled to 25°C is attached to a polyethylene terephthalate film is 50% or more of the initial adhesive force a when the adhesive surface of the adhesive tape is attached to the polyethylene terephthalate film at an ambient temperature of 25°C.
[0020] In one embodiment, the adhesive force c when the adhesive surface of the adhesive tape of the present invention is attached to a polyethylene terephthalate film after the cycle of heating to 130°C and then cooling to 25°C is performed twice is 50% or more of the initial adhesive force a when the adhesive surface of the adhesive tape is attached to the polyethylene terephthalate film at an ambient temperature of 25°C.
[0021] In one embodiment, the pressure-sensitive adhesive tape includes the pressure-sensitive adhesive layer on both sides of the substrate.
[0022] In one embodiment, the pressure-sensitive adhesive layer is provided on one side of the substrate, and another pressure-sensitive adhesive layer is provided on the other side of the substrate.
[0023] Effects of the Invention
[0024] According to the present invention, a pressure-sensitive adhesive tape capable of preventing a pressure-sensitive adhesive layer from floating off a substrate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic cross-sectional view of a pressure-sensitive adhesive tape according to one embodiment of the present invention. DETAILED DESCRIPTION
[0026] A. Overall composition of adhesive tape
[0027] Figure 1 (a) and (b) are schematic cross-sectional views of an adhesive tape according to an embodiment of the present invention. The adhesive tape 100 includes a substrate 10 and an adhesive layer 20 disposed on at least one side of the substrate 10 . Figure 1 (c) is a schematic cross-sectional view of an adhesive tape according to another embodiment of the present invention. The adhesive tape 200 comprises an adhesive layer 10 and another adhesive layer 30 disposed on at least one side of the adhesive layer 10. Although not shown in the figure, the adhesive tape may further comprise an elastic layer (hereinafter referred to as item E) capable of imparting elasticity to the adhesive tape, a separator (hereinafter referred to as item F) disposed on the adhesive layer in a removable manner, etc. as a layer other than the adhesive layer.
[0028] Above-mentioned adhesive layer comprises heat-expandable microsphere.This heat-expandable microsphere can expand under the prescribed temperature.The adhesive layer that comprises this heat-expandable microsphere expands heat-expandable microsphere by being heated to more than the prescribed temperature, produces concavo-convex on the bonding surface (i.e. adhesive layer surface), and adhesive force reduces or disappears.For example, when the test of electronic components (for example ceramic capacitors), when processing, etc., adhesive tape of the present invention is used as the temporary fixing sheet of the tested body or the processed object, under the situation of needing fixing, show necessary adhesiveness, thereafter, when peeling off the adhesive tape, adhesive force is reduced or disappears by heating, show good peelability.
[0029] At an ambient temperature of 25°C, the initial adhesive force a when the adhesive surface of the adhesive tape of the present invention is attached to a polyethylene terephthalate film (e.g., a thickness of 25 μm) is preferably 1.5 N / 20 mm to 20 N / 20 mm, more preferably 1.5 N / 20 mm to 18 N / 20 mm, and further preferably 2.0 N / 20 mm to 12 N / 20 mm. If it is in this range, an adhesive tape useful as a temporary fixing sheet used in the manufacture of electronic components can be obtained. In this specification, the initial adhesive force refers to the adhesive force in a state that has not yet undergone a thermal history of 50°C or more. In addition, the adhesive force refers to the adhesive force measured by the method based on JIS Z 0237:2000 (lamination conditions: 2 kg roller back and forth once, stretching speed: 300 mm / min, peeling angle: 180°).
[0030] When the adhesive surface of the adhesive tape of the present invention is attached to a polyethylene terephthalate film (e.g., 25 μm thick) after being heated to 130° C. and then cooled to 25° C., the adhesive force b is 0.75 N / 20 mm to 20 N / 20 mm, more preferably 0.75 N / 20 mm to 18 N / 20 mm, and even more preferably 1.0 N / 20 mm to 12 N / 20 mm.
[0031] When the adhesive surface of the adhesive tape of the present invention is attached to a polyethylene terephthalate film (for example, 25 μm thick) after being heated to 130° C. and then cooled to 25° C., the adhesive strength b is preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more of the initial adhesive strength a.
[0032] When the adhesive surface of the adhesive tape of the present invention is attached to a polyethylene terephthalate film (e.g., 25 μm thick) after two cycles of heating to 130°C and then cooling to 25°C are subjected to, the adhesive force c is 0.75 N / 20 mm to 20 N / 20 mm, more preferably 0.75 N / 20 mm to 18 N / 20 mm, and even more preferably 1.0 N / 20 mm to 12 N / 20 mm.
[0033] When the adhesive surface of the adhesive tape of the present invention is attached to a polyethylene terephthalate film (e.g., 25 μm thick) after two cycles of heating to 130°C and then cooling to 25°C, the adhesive strength c is preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more relative to the initial adhesive strength a.
[0034] The thickness of the pressure-sensitive adhesive tape of the present invention is preferably 30 μm to 500 μm, more preferably 40 μm to 300 μm.
[0035] B. Adhesive layer
[0036] As described above, the adhesive layer contains heat-expandable microspheres. From a practical point of view, the adhesive layer further contains an adhesive.
[0037] B-1. Heat-expandable microspheres
[0038] The heat-expandable microspheres are composed of a shell and a volatile substance (typically, an organic solvent) contained in the shell.
[0039] The resin constituting the shell includes a structural unit having a carboxyl group. If the shell is constituted by a resin having a carboxyl group, the carboxyl group interacts with the base polymer constituting the adhesive in the adhesive layer, giving cohesion to the adhesive. As a result, in the adhesive tape of the present invention, the deformation of the adhesive layer is suppressed, and the adhesive layer can also be prevented from floating or detaching from the substrate at high temperatures. If such an adhesive tape of the present invention is used, residual glue on the adherend during heat peeling can be prevented. The structural unit having a carboxyl group can be a structural unit derived from a carboxyl group-containing monomer such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, etc.
[0040] The resin constituting the shell may further include a structural unit derived from a monomer capable of free radical polymerization in addition to a structural unit having a carboxyl group. As the monomer, for example, nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaric acid nitrile can be listed; vinylidene chloride; vinyl acetate; (meth) acrylate methyl, (meth) acrylate ethyl, (meth) acrylate n-butyl, (meth) acrylate isobutyl, (meth) acrylate tert-butyl, (meth) acrylate isobornyl, (meth) acrylate cyclohexyl, (meth) acrylate benzyl, acrylate β-carboxyethyl acrylate and other (meth) acrylate esters; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide, etc. In one embodiment, the resin constituting the shell includes: a structural unit having a carboxyl group; and at least one selected from the group consisting of a structural unit derived from isobornyl acrylate, a structural unit derived from methacrylonitrile, a structural unit derived from acrylonitrile, a structural unit derived from methyl (meth) acrylate, and a structural unit derived from vinylidene chloride. The resin constituting the shell preferably contains a structural unit having a carboxyl group and a structural unit derived from methacrylonitrile and / or acrylonitrile.
[0041] In the resin constituting the above-mentioned shell, the content ratio of the structural unit with carboxyl is preferably 5 to 97 parts by weight relative to 100 parts by weight of resin, more preferably 5 to 90 parts by weight, further preferably 5 to 85 parts by weight, particularly preferably 5 to 80 parts by weight, and most preferably 10 to 75 parts by weight. If this range, then under the state of controlling the productivity and particle size of the heat-expandable microspheres, the deformation of the adhesive layer is suppressed, and it is also possible to prevent the adhesive layer from floating or detaching from the substrate at high temperatures. If the content ratio of the structural unit with carboxyl is less than the above-mentioned range, then the ratio of the carboxyl retained in the heat-expandable microspheres may be reduced, and the interaction with the base polymer in the adhesive is insufficient, and the above-mentioned effect cannot be obtained. If the content ratio of the structural unit with carboxyl is more than the above-mentioned range, then it is possible to be difficult to control reactivity and particle size when manufacturing heat-expandable microspheres, and productivity is reduced.
[0042] The resin forming the shell may be a cross-linked body. The excluded free volume of the polymer can be adjusted by cross-linking, thereby controlling the diffusivity of the contained volatile substances, the expansibility of the shell, etc. The cross-linked body may further include a structural unit derived from a monomer having two or more polymerizable double bonds in the molecule. In one embodiment, the above-mentioned monomer capable of free radical polymerization and a monomer having two or more polymerizable double bonds in the molecule are used in combination. Examples of the monomer having two or more polymerizable double bonds in the molecule include aromatic divinyl compounds such as divinylbenzene and divinylnaphthalene; allyl methacrylate, triacryloyl formal, triallyl isocyanate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, PEG#200 di(meth)acrylate, PEG#400 di(meth)acrylate, PEG#600 di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, glycerol di(meth)acrylate, dimethylol-tricyclodecane di(meth)acrylate, ) acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, neopentyl glycol acrylate benzoate, trimethylolpropane acrylate benzoate, (meth)acrylate 2-hydroxy-3-acryloxypropyl, hydroxypivalate neopentyl glycol di(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, phenyl glycidyl ether acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether acrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, etc.
[0043] The glass transition temperature (Tg) of the resin constituting the above-mentioned shell is preferably above 120°C, more preferably above 125°C, further preferably above 130°C, and particularly preferably above 135°C. By using heat-expandable microspheres containing a shell having such a glass transition temperature, it is possible to obtain an adhesive tape in which the foaming temperature of the heat-expandable microspheres is difficult to vary. In more detail, when the conventional blowing agent is heated below the foaming temperature, there is a tendency for the foaming temperature to decrease due to the thermal history, but by using heat-expandable microspheres containing the above-mentioned shell, the decrease in foaming temperature caused by the thermal history can be prevented. The above-mentioned glass transition temperature can be calculated by Fox's calculation formula. As shown below, Fox's calculation formula refers to: the glass transition temperature Tg (°C) of the copolymer and the glass transition temperature Tg (°C) of the homopolymer obtained by homopolymerizing the monomers (monomers) constituting the copolymer i It should be noted that in the following Fox formula, Tg (°C) represents the glass transition temperature of the copolymer, W i represents the weight fraction of monomer i, Tg i (°C) represents the glass transition temperature of the homopolymer formed from monomer i.
[0044] 1 / (273+Tg)=Σ(W i / (273+Tg i ))
[0045] As the glass transition temperature of the homopolymer formed by the monomers, methacrylic acid homopolymer: 228°C, acrylonitrile homopolymer: 97°C, methyl methacrylate homopolymer: 102°C, methacrylonitrile homopolymer: 120°C, vinylidene chloride homopolymer: 75°C, isobornyl acrylate homopolymer: 97°C. In addition, as the glass transition temperature of homopolymers other than these, the values described in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc, 1999) can be used. It should be noted that when multiple Tg values are described in the document, the "conventional" value is used.
[0046] The thickness of the shell is preferably 1 μm to 15 μm, more preferably 1 μm to 7 μm, and even more preferably 1 μm to 5 μm.
[0047] Typically, the volatile substance contained in the shell is an organic solvent. Examples of the organic solvent include straight-chain aliphatic hydrocarbons with 3 to 8 carbon atoms and their fluorides, branched aliphatic hydrocarbons with 3 to 8 carbon atoms and their fluorides, straight-chain alicyclic hydrocarbons with 3 to 8 carbon atoms and their fluorides, ether compounds having a hydrocarbon group with 2 to 8 carbon atoms, or compounds in which a portion of the hydrogen atoms of the hydrocarbon group are replaced by fluorine atoms. In one embodiment, as an organic solvent, hydrocarbons consisting only of hydrogen atoms and carbon atoms such as propane, cyclopropane, butane, cyclobutane, isobutane, pentane, cyclopentane, neopentane, isopentane, hexane, cyclohexane, 2-methylpentane, 2,2-dimethylbutane, heptane, cycloheptane, octane, cyclooctane, methylheptanes, trimethylpentanes, etc.; hydrofluoroethers such as C3F7OCH3, C4F9OCH3, and C4F9OC2H5, etc. can be used. These organic solvents may be used alone or in combination of two or more. The above organic solvents have the following advantages: low affinity with the resin and / or adhesive forming the shell, difficulty in dissolving the shell and / or adhesive, and difficulty in changing the physical properties such as thermal properties. In addition, from the viewpoint of industrial utilization, hydrocarbons consisting only of hydrogen atoms and carbon atoms are preferred.
[0048] In one embodiment, as hydrocarbons composed only of hydrogen atoms and carbon atoms, branched hydrocarbons (such as isobutane, isopentane, etc.) can be used. Branched hydrocarbons are not easily charged, and if such solvents are used, accidents such as fires caused by charging can be prevented.
[0049] The boiling point of the organic solvent is preferably -50°C to 100°C, more preferably -20°C to 100°C. If this range is used, the heat-expandable microspheres can be obtained in which the shell can be well expanded without being destroyed. It should be noted that when the boiling point of the organic solvent is too low, the operation for suppressing the volatilization during the manufacture of the heat-expandable microspheres may become complicated.
[0050] The difference (Tg-bp) between the boiling point (bp) of the organic solvent and the glass transition temperature (Tg) of the resin constituting the shell is preferably above 0°C, more preferably 0°C to 200°C, and further preferably 50°C to 150°C. If an organic solvent having a boiling point higher than the glass transition temperature of the shell is used, the shell may be destroyed due to the pressure generated when the organic solvent is heated, and the adhesive may scatter, etc., thereby hindering the expected functions and effects of the present application. It should be noted that when two or more organic solvents (mixed solvents) are used, the "boiling point (bp) of the organic solvent" refers to the value calculated by (the sum of the boiling points of each organic solvent) / (the number of types of organic solvents).
[0051] The containing ratio of above-mentioned organic solvent is preferably 5 wt %~35 wt %, more preferably 10 wt %~30 wt % relative to the weight before the heating of heat-expandable microsphere.If be this scope, then can obtain the thermal expansibility that can stably expand.When containing ratio is less than 5 wt %, the expansion when might be heated is insufficient, is difficult to form adhesive concavo-convex, and heating peeling occurs badly, produces residual glue.When containing ratio surpasses 35 wt %, the expansion when might be heated becomes too large, and adhesive layer peels off from base material.
[0052] At an ambient temperature of 25°C, the average particle size (number basis) of the heat-expandable microspheres before the heat-expandable microspheres are foamed is preferably 5μm to 30μm, more preferably 5μm to 28μm, and further preferably 10μm to 25μm. If it is in this range, heat-expandable microspheres with high dispersibility in the adhesive layer can be obtained. The adhesive layer containing heat-expandable microspheres in a highly dispersible state has high uniformity of unevenness caused by heating, and can exhibit excellent peelability. The average particle size of the heat-expandable microspheres can be controlled by, for example, the conditions when the heat-expandable microspheres are polymerized (see below for details). The average particle size can be measured by the particle size distribution measurement method in the laser scattering method. More specifically, the average particle size can be measured as follows: after dispersing the heat-expandable microspheres used in a specified solvent (e.g., water), a particle size distribution measuring device (e.g., trade name "SALD-2000J" manufactured by Shimadzu Corporation) is used to measure.
[0053] The foaming temperature of the heat-expandable microspheres is preferably 150 to 280° C., more preferably 155 to 260° C. In the present specification, the foaming temperature of the heat-expandable microspheres may correspond to the temperature at which the adhesive force of the adhesive tape reaches 1.0 N / 20 mm or less and 50% or less of the initial adhesive force.
[0054] In one embodiment, the content ratio of heat-expandable microspheres is expressed by the area ratio of heat-expandable microspheres measured from the cross section. When the cross-sectional area of the adhesive layer in the specified cross section is set to A and the cross-sectional area of the heat-expandable microspheres in the cross section is set to B, the ratio of the cross-sectional area B of the heat-expandable microspheres relative to the cross-sectional area A of the adhesive layer is preferably 3% to 75%, and more preferably 3.5% to 70%. When the ratio of cross-sectional area B is less than 3%, it is possible that even if the heat-expandable microspheres are expanded by heating, the concavoconvexity generated on the adhesive surface is insufficient, and the desired peelability cannot be obtained. On the other hand, when the ratio of cross-sectional area B exceeds 75%, it is possible that the volume change of the adhesive layer becomes too large, and floating / peeling occurs between the substrate and the adhesive layer. In addition, it is possible that the adhesive content ratio in the adhesive layer is low, and the desired adhesive force cannot be obtained. It should be noted that the ratio of the cross-sectional area B of the heat-expandable microspheres can be obtained as follows: for example, using an electron microscope (e.g., Hitachi Science and Technology Co., Ltd., trade name "S-3400N low vacuum scanning electron microscope") to observe the cross section of the adhesive layer, and the image obtained thereby is appropriately processed to obtain. For example, the image is output on paper and the weight a of the adhesive layer (i.e., the entire adhesive layer containing heat-expandable microspheres) and the weight b of the paper obtained by cutting out only the heat-expandable microspheres are calculated using the formula b / a×100.
[0055] The content ratio of heat-expandable microsphere is preferably 5 to 80 parts by weight relative to 100 parts by weight of adhesive layer, more preferably 5 to 60 parts by weight, and further preferably 10 to 50 parts by weight. If it is this range, the ratio of the cross-sectional area B of the heat-expandable microsphere as described above can be achieved. In addition, in order to set the content ratio of heat-expandable microsphere to the above range, and not to make the heat-expandable microsphere exist in the adhesive layer, by stirring the adhesive layer forming composition until before the coating process is about to be carried out, the cross-sectional area B of the heat-expandable microsphere can be set to the preferred range. The content ratio of heat-expandable microsphere is obtained by the following formula. The weight of the heat-expandable microsphere is obtained by measuring the weight of the heat-expandable microsphere taken out from the adhesive layer.
[0056] Content ratio of heat-expandable microspheres (weight %) = weight of heat-expandable microspheres / weight of adhesive layer × 100
[0057] The above-mentioned heat-expandable microsphere can be manufactured by any and appropriate method. In one embodiment, the above-mentioned heat-expandable microsphere is obtained by suspension polymerization. Suspension polymerization is usually carried out by making monomer (shell forming material) and organic solvent dispersed in the aqueous dispersion medium containing dispersant, and in the presence of organic solvent, monomer polymerization is carried out. In addition, the dispersion stabilizer that makes dispersion stability can also be utilized. As the dispersion stabilizer in the aqueous dispersion medium, inorganic particles such as silicon dioxide, magnesium hydroxide, calcium phosphate, aluminum hydroxide, etc. can be listed. In addition, as a dispersion stabilization auxiliary agent, for example, a condensation product of diethanolamine and aliphatic dicarboxylic acid, polyvinyl pyrrolidone, methylcellulose, polyethylene oxide, polyvinyl alcohol, various emulsifiers, etc. can be used.
[0058] Can utilize the polymerization condition of above-mentioned suspension polymerization, the kind / addition of mixed component etc. to control the characteristics of heat-expandable microspheres such as the content of particle diameter, organic solvent.For example, by the operations such as stirring speed when reducing the addition of dispersion agent, slowing down polymerization, thereby can obtain the heat-expandable microsphere of large particle diameter.In addition, if increase the compounding amount of monomer or the stirring speed when slowing down polymerization, then can obtain the heat-expandable microsphere that the thickness of shell is large.
[0059] B-2. Adhesive
[0060] As the adhesive constituting the above-mentioned adhesive layer, any and appropriate adhesive can be used as long as the effect of the present invention can be obtained. As the above-mentioned adhesive, for example, acrylic adhesives, silicone adhesives, vinyl alkyl ether adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, fluorine adhesives, styrene-diene block copolymer adhesives, active energy ray curing adhesives, etc. can be listed. Among them, acrylic adhesives, rubber adhesives or silicone adhesives are preferred, and acrylic adhesives are more preferred.
[0061] The gel fraction of the above-mentioned adhesive is preferably 20% by weight to 100% by weight, more preferably 30% by weight to 99% by weight, and further preferably 50% by weight to 99% by weight. When the gel fraction is less than 20% by weight, even if the heat-expandable microspheres expand and produce concavoconvex on the adhesive layer surface, the adhesive layer is also likely to flow and make the concavoconvex disappear in a short time. On the other hand, when the gel fraction exceeds 99% by weight, it is possible to hinder the heat expansion of the heat-expandable microspheres without producing sufficient concavoconvex, or even when producing concavoconvex, the heat-expandable microspheres will explode and the shell of the heat-expandable microspheres, the surrounding adhesive layer will scatter, and the residual adhesive will deteriorate. The gel fraction of the adhesive can be controlled by adjusting the composition of the base polymer constituting the adhesive, the kind, content, and kind, content of the crosslinking agent added to the adhesive. The determination method of the gel fraction is as follows.
[0062] About 0.1 g of the adhesive was sampled and accurately weighed (the weight of the sample), and the sample was wrapped with a mesh sheet (trade name "NTF-1122", manufactured by Nitto Denko Corporation), and then immersed in about 50 ml of toluene at room temperature for one week. Thereafter, the solvent-insoluble component (the content of the mesh sheet) was taken out from the toluene, dried at 70° C. for about 5 hours, and the solvent-insoluble component after drying was weighed (weight after immersion and drying), and the gel fraction (weight %) was calculated by the following formula (a).
[0063] Gel fraction (weight %) = [(weight after immersion and drying) / (weight of sample)] × 100 (a)
[0064] The base polymer included in the above-mentioned adhesive preferably has OH group or COOH group.If use this base polymer, then effect of the present invention becomes more remarkable.In addition, if use the above-mentioned base polymer, then can use cross-linking agent to adjust the above-mentioned gel fraction.In addition, can utilize the amount of OH group or COOH group that do not react with cross-linking agent to adjust the cohesiveness of the base polymer based on intermolecular forces such as hydrogen bond.Thus, can control the concavo-convex shape of the adhesive surface that produces because of the expansion of heat-expandable microsphere.
[0065] The acid value of the base polymer is preferably 0 to 100, more preferably 10 to 80, and even more preferably 20 to 50. The acid value of the polymer in the adhesive layer can be measured by extracting the solvent-soluble component in the adhesive layer. Specifically, the solvent-soluble component can be extracted by the following method.
[0066] (i) The pressure-sensitive adhesive layer is placed in a solvent to prepare a solution sample in which the solvent-soluble component in the pressure-sensitive adhesive layer is dissolved in the solvent.
[0067] As a solvent, taking into account polarity, etc., any one solvent selected from chloroform (CHCl3), dichloromethane (CH2Cl2), tetrahydrofuran (THF), acetone, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), methanol, ethanol, toluene and water, or a mixed solvent of two or more thereof can be used in any ratio.
[0068] Typically, about 30 mL of solvent is added to about 0.2 g of the adhesive layer, and stirred for about 30 minutes to 12 hours in a temperature range from room temperature to about the boiling point of the solvent used. If necessary, for example, when the extraction efficiency of the component to be analyzed is low, the sample after the above solution is separated can be re-added with a solvent in an amount substantially equal to the separated solution and stirred, and the operation of separating the solution is repeated once or more to prepare a solution sample.
[0069] (ii) The solvent-soluble polymer can be taken out by removing the solvent from the solution sample by evaporation or the like.
[0070] It should be noted that the solvent-soluble polymer sometimes contains solvent-soluble components such as low molecular weight components of unreacted crosslinking agents that are not the subject of measurement. In this case, a solvent-soluble polymer consisting only of the subject of measurement is prepared by a method of immersing the above-mentioned solution sample in a solvent in which only the polymer component is insoluble (reprecipitation method), molecular weight fractionation (fractionation liquid chromatography) using gel filtration chromatography of the above-mentioned solution sample, etc.
[0071] (Acrylic adhesive)
[0072] Examples of the acrylic pressure-sensitive adhesive include those containing, as a base polymer, an acrylic polymer (homopolymer or copolymer) using one or more kinds of (meth)acrylic acid alkyl esters as monomer components. Specific examples of the alkyl (meth)acrylate include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, alkyl (meth)acrylates having a linear or branched alkyl group having 4 to 18 carbon atoms can be preferably used.
[0073] In the acrylic polymer, for the purpose of improving cohesion, heat resistance, crosslinking, etc., units corresponding to other monomers that can be copolymerized with the above-mentioned alkyl (meth)acrylate may be included as needed. Examples of such monomers include carboxyl-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itaconic anhydride; hydroxyl-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide Sulfonic acid group-containing monomers such as propanesulfonic acid, (meth) sulfopropyl acrylate, (meth) acryloxynaphthalenesulfonic acid, etc.; (meth) acrylamide, N,N-dimethyl (meth) acrylamide, N-butyl (meth) acrylamide, N-hydroxymethyl (meth) acrylamide, N-hydroxymethylpropane (meth) acrylamide, etc. (N-substituted) amide monomers; (meth) acrylate aminoalkyl ester monomers such as (meth) aminoethyl acrylate, (meth) acrylate-N,N-dimethylaminoethyl ester, (meth) acrylate tert-butylaminoethyl ester; (meth) acrylate alkoxyalkyl ester monomers such as (meth) methoxyethyl acrylate, (meth) ethoxyethyl acrylate; N-cyclopentyl acrylate Maleimide monomers such as hexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; vinyl acetate, vinyl propionate, Vinyl monomers such as N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinylcarboxylic acid amides, styrene, α-methylstyrene, and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy-containing acrylic monomers such as glycidyl (meth)acrylate; diol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate;Acrylate monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., such as tetrahydrofurfuryl (meth)acrylate, fluoro (meth)acrylate, and silicone (meth)acrylate; polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin monomers such as isoprene, butadiene, and isobutylene; vinyl ether monomers such as vinyl ether, etc. These monomers can be used alone or in combination of two or more. ;
[0074] (Silicone adhesive)
[0075] As the above-mentioned silicone adhesive, any and appropriate adhesive can be used as long as the effect of the present invention can be obtained. As the above-mentioned silicone adhesive, it is preferred to use a silicone adhesive having, for example, a silicone rubber or silicone resin containing an organopolysiloxane as a base polymer. As the base polymer constituting the silicone adhesive, a base polymer obtained by cross-linking the above-mentioned silicone rubber or silicone resin can be used. It should be noted that in this specification, "silicone rubber" refers to a polymer obtained by linking a diorganosiloxane (D unit) as a main component into a straight chain (for example, a viscosity of 1000 Pa·s), and "silicone resin" refers to a polymer composed of a triorganosilhemioxane (M unit) and a silicate (Q unit) as a main component ("Material Design and Functionality of Adhesives (Films / Tapes)", Technical Information Association, published on September 30, 2009).
[0076] Examples of the above-mentioned silicone rubber include organopolysiloxanes containing dimethylsiloxane as a structural unit. Functional groups (e.g., vinyl groups) may be introduced into the organopolysiloxane as needed. The weight average molecular weight of the organopolysiloxane is preferably 100,000 to 1,000,000, more preferably 150,000 to 500,000. The weight average molecular weight can be measured by GPC (solvent: THF).
[0077] Examples of the silicone resin include a resin selected from R3SiO 1 / 2 Structural unit, SiO2 structural unit, RSiO 3 / 2 An organopolysiloxane having at least one structural unit of a R2SiO structural unit and a R2SiO structural unit (R is a monovalent hydrocarbon group or a hydroxyl group).
[0078] The above-mentioned silicone rubber and silicone resin can be used in combination. The weight ratio of silicone rubber to silicone resin in the silicone adhesive (rubber: resin) is preferably 100:0 to 100:220, more preferably 100:0 to 100:180, and further preferably 100:10 to 100:100. The silicone rubber and silicone resin can be included in the silicone adhesive in the form of a simple mixture, or in the form of a partial condensation of the silicone rubber and the silicone resin. The rubber: resin ratio can also be adjusted by 29 The ratio of the Q unit (resin) to the D unit (rubber) obtained by Si-NMR measurement of the composition of the silicone adhesive is determined.
[0079] (Rubber-based adhesive)
[0080] As the above-mentioned rubber-based adhesive, any and appropriate adhesive can be used as long as the effect of the present invention can be obtained. As the above-mentioned rubber-based adhesive, it is preferred to use a rubber-based adhesive such as the following rubber as a base polymer: natural rubber; polyisoprene rubber, butadiene rubber, styrene-butadiene (SB) rubber, styrene-isoprene (SI) rubber, styrene-isoprene-styrene block copolymer (SIS) rubber, styrene-butadiene-styrene block copolymer (SBS) rubber, styrene-ethylene-butylene-styrene block copolymer (SEBS) rubber, styrene-ethylene-propylene-styrene block copolymer (SEPS) rubber, styrene-ethylene-propylene-styrene block copolymer (SEP) rubber, recycled rubber, butyl rubber, polyisobutylene rubber, or synthetic rubbers such as modified products thereof.
[0081] (additive)
[0082] The adhesive may contain any and appropriate additives as required. Examples of the additives include crosslinking agents, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, ultraviolet light absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.
[0083] As the above-mentioned tackifier, any appropriate tackifier can be used. As the tackifier, for example, a tackifier resin can be used. Specific examples of the tackifying resin include rosin-based tackifying resins (e.g., unmodified rosin, modified rosin, rosin phenol-based resins, rosin ester-based resins, etc.), terpene-based tackifying resins (e.g., terpene-based resins, terpene phenol-based resins, styrene-modified terpene-based resins, aromatic-modified terpene-based resins, hydrogenated terpene-based resins), hydrocarbon-based tackifying resins (e.g., aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (e.g., styrene resins, xylene-based resins, etc.), aliphatic-aromatic petroleum resins, aliphatic-alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, coumarone indene resins, etc.), phenol-based tackifying resins (e.g., alkylphenol-based resins, xylene formaldehyde-based resins, resol phenolic resins, novolacs, etc.), ketone-based tackifying resins, polyamide-based tackifying resins, epoxy-based tackifying resins, elastic-based tackifying resins, etc.
[0084] The amount of the thickener added is preferably 5 to 100 parts by weight, more preferably 5 to 50 parts by weight, based on 100 parts by weight of the base polymer.
[0085] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, and amine crosslinking agents. Among them, an isocyanate crosslinking agent or an epoxy crosslinking agent is preferred.
[0086] Specific examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name "CORONATE L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name "CORONATE HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industries, Ltd., trade name "CORONATE HX"), etc. The content of the isocyanate crosslinking agent can be set to any appropriate amount depending on the desired adhesive force, elasticity of the adhesive layer, etc., and is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the base polymer.
[0087] Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOLIGHT 1500NP"), and polyoxyethylene glycol diglycidyl ether. E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, and the like. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive force, elasticity of the adhesive layer, etc., and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, relative to 100 parts by weight of the base polymer.
[0088] As the above-mentioned plasticizer, any and appropriate plasticizer can be used. As specific examples of plasticizers, for example, trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, polyester plasticizers, adipic acid plasticizers, etc. can be cited. Among them, trimellitic acid ester plasticizers (such as trimellitic acid tri (n-octyl ester), trimellitic acid tri (2-ethylhexyl ester), etc.) or pyromellitic acid ester plasticizers (such as pyromellitic acid tetra (n-octyl ester), pyromellitic acid tetra (2-ethylhexyl ester), etc.) are preferred. Plasticizers can be used alone or in combination of two or more. The content of the plasticizer is preferably 1 to 20 parts by weight relative to 100 parts by weight of the base polymer, and more preferably 1 to 5 parts by weight.
[0089] B-3. Characteristics of adhesive layer
[0090] The elastic modulus of the above-mentioned adhesive layer based on the nanoindentation method at 23°C is preferably 0.1MPa to 500MPa, and more preferably 0.5MPa to 400MPa. The elastic modulus based on the nanoindentation method is obtained as follows: the portion about 3μm inside from the surface of the adhesive layer and where there are no heat-expandable microspheres (the portion more than 1μm away from the shell surface of the heat-expandable microspheres) is taken as the measurement object, and the indenter is pressed against the adhesive layer. The load and indentation depth of the indenter at this time are continuously measured during loading and unloading, and the load-indentation depth curve obtained is obtained. In this specification, the elastic modulus based on the nanoindentation method refers to the elastic modulus obtained by setting the measurement conditions to load / unload speed: 1000nm / s, indentation depth: 800nm, and measuring as above.
[0091] The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 300 μm, more preferably 5 μm to 250 μm, further preferably 5 μm to 100 μm, and particularly preferably 5 μm to 60 μm.
[0092] B-4. Other ingredients
[0093] The above-mentioned adhesive layer may further contain any and appropriate other components as long as the effect of the present invention can be obtained. As other components, beads, for example, can be listed. As the beads, for example, glass beads, resin beads, etc. can be listed. If such beads are added to the adhesive layer, an adhesive tape that can improve the elastic modulus of the adhesive layer and can process the workpiece with better precision can be obtained. The average particle size of the beads is, for example, 0.01 μm to 50 μm. The amount of beads added is, for example, 10 to 200 parts by weight, preferably 20 to 100 parts by weight, relative to 100 parts by weight of the adhesive layer.
[0094] C. Base material
[0095] As the above-mentioned substrate, for example, resin sheets, nonwoven fabrics, paper, metal foil, woven fabrics, rubber sheets, foam sheets, and laminates thereof (especially laminates containing resin sheets) can be cited. As the resin constituting the resin sheet, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyimide (PI), polyvinyl chloride (PVC), polyphenylene sulfide (PPS), fluorine resin, polyether ether ketone (PEEK), etc. can be cited. As nonwoven fabrics, nonwoven fabrics based on natural fibers with heat resistance, such as nonwoven fabrics containing Manila hemp, synthetic resin nonwoven fabrics such as polypropylene resin nonwoven fabrics, polyethylene resin nonwoven fabrics, and ester resin nonwoven fabrics can be cited. As metal foils, copper foils, stainless steel foils, aluminum foils, etc. can be cited. Examples of paper include Japanese paper and kraft paper.
[0096] The thickness of the substrate can be set to any appropriate thickness according to the desired strength or flexibility, the purpose of use, etc. The thickness of the substrate is preferably 1000 μm or less, more preferably 1 μm to 1000 μm, further preferably 1 μm to 500 μm, particularly preferably 3 μm to 300 μm, and most preferably 5 μm to 250 μm.
[0097] The substrate may be subjected to a surface treatment, such as corona treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, and primer coating treatment.
[0098] As the above-mentioned organic coating material, for example, the materials described in Plastic Hard Coating Material II (CMC Publishing, (2004)) can be cited. Preferably, a carbamate polymer is used, and more preferably, polyacrylic carbamate, polyester carbamate or their precursors are used. This is because the coating / applying on the substrate is simple, and a variety of materials can be selected industrially and can be obtained cheaply. The carbamate polymer is, for example, a polymer formed by a reaction mixture of an isocyanate monomer and an alcoholic hydroxyl-containing monomer (for example, a hydroxyl-containing acrylic compound or a hydroxyl-containing ester compound). In the organic coating material, as optional additives, chain extenders such as polyamines, antioxidants, oxidation stabilizers, etc. can be included. The thickness of the organic coating layer is not particularly limited, for example, it is suitable to be about 0.1μm to 10μm, preferably about 0.1μm to 5μm, and more preferably about 0.5μm to 5μm.
[0099] D. Additional Adhesive Layer
[0100] As the above-mentioned other adhesive layer, any and appropriate adhesive layer can be formed. As the adhesive forming the other adhesive layer, for example, rubber adhesive, acrylic adhesive, vinyl alkyl ether adhesive, silicone adhesive, polyester adhesive, polyamide adhesive, urethane adhesive, fluorine adhesive, styrene-diene block copolymer adhesive, etc. can be listed. For example, known or commonly used additives such as plasticizers, fillers, surfactants, antioxidants, and adhesion imparting agents can be mixed into the adhesive.
[0101] The thickness of the additional pressure-sensitive adhesive layer is preferably 300 μm or less, more preferably 1 μm to 300 μm, and even more preferably 5 μm to 100 μm.
[0102] E. Elastic layer
[0103] The adhesive tape of the present invention may further include an elastic layer. The elastic layer may be disposed on one side of the adhesive layer. When the adhesive tape includes a substrate, the elastic layer may be disposed between the adhesive layer and the substrate. By including the elastic layer, the followability of the adherend is improved. In addition, when the adhesive tape with the elastic layer is heated during peeling, the deformation (expansion) of the surface direction of the adhesive layer is constrained, and deformation in the thickness direction occurs preferentially. As a result, the peelability is improved.
[0104] The elastic layer includes a base polymer, and as the base polymer, the polymer exemplified as the base polymer constituting the adhesive layer can be used. In one embodiment, the elastic layer may include natural rubber, synthetic rubber, synthetic resin, etc. As the synthetic rubber and synthetic resin, there can be listed nitrile, diene, and acrylic synthetic rubbers; thermoplastic elastomers such as polyolefins and polyesters; ethylene-vinyl acetate copolymers; polyurethanes; polybutadiene; soft polyvinyl chloride, etc. The base polymer constituting the elastic layer may be the same as or different from the base polymer forming the adhesive layer. The elastic layer may be a foamed film formed by the base polymer. The foamed film can be obtained by any and appropriate method. It should be noted that the elastic layer and the adhesive layer can be distinguished by the difference in base polymers and / or the presence or absence of a foaming agent (the elastic layer does not contain a foaming agent). In more detail, in the case where the elastic layer and the adhesive layer are formed by different base polymers and the interface between the elastic layer and the adhesive layer can be identified by cross-sectional observation, the boundary between the elastic layer and the adhesive layer is defined by the interface. When the interface between the elastic layer and the pressure-sensitive adhesive layer cannot be identified by cross-sectional observation, the region where the foaming agent is observed by cross-sectional observation is the pressure-sensitive adhesive layer.
[0105] The elastic layer may contain any appropriate additives as required. Examples of such additives include crosslinking agents, vulcanizing agents, tackifying resins, plasticizers, softeners, fillers, antioxidants, etc. When a hard resin such as polyvinyl chloride is used as the base polymer, it is preferred to use a plasticizer and / or softener in combination to form an elastic layer having desired elasticity.
[0106] The thickness of the elastic layer is preferably 3 μm to 200 μm, more preferably 5 μm to 100 μm. Within this range, the above-mentioned function of the elastic layer can be fully exhibited.
[0107] The elastic modulus of the elastic layer at 25° C. is preferably 0.01 MPa to 500 MPa, more preferably 0.05 MPa to 500 MPa, and even more preferably 0.1 MPa to 500 MPa. Within this range, the elastic layer can fully exert the above-mentioned function. It should be noted that the tensile elastic modulus can be measured according to JIS K7161:2008.
[0108] F.Separator
[0109] The adhesive tape of the present invention may further include a separator as required. At least one surface of the separator may be a release surface, and may be provided to protect the adhesive layer. The separator may be made of any appropriate material.
[0110] G. Method for manufacturing adhesive tape
[0111] The adhesive tape of the present invention can be manufactured by any and appropriate method. About the adhesive tape of the present invention, for example, the following method can be cited: a method of directly coating a composition for forming an adhesive layer comprising an adhesive and heat-expandable microspheres on a substrate; or, a method of transferring a coating layer formed by coating an adhesive layer forming composition on an arbitrary and appropriate substrate to a substrate, etc. The adhesive layer forming composition can include any and appropriate solvent. In addition, after forming an adhesive coating layer using a composition comprising an adhesive, heat-expandable microspheres are sprinkled on the adhesive coating layer, and then the heat-expandable microspheres are embedded in the coating layer using a laminator, so that an adhesive layer comprising heat-expandable microspheres can be formed.
[0112] The content of the heat-expandable microspheres in the adhesive layer-forming composition is preferably 5 to 95 wt %, more preferably 10 to 70 wt %, and further preferably 10 to 50 wt %, based on the solid content weight of the adhesive layer-forming composition.
[0113] When the adhesive layer has the elastic layer, the elastic layer can be formed by, for example, applying a composition for forming an elastic layer on a substrate or on the adhesive layer.
[0114] As the coating method of each of the above-mentioned compositions, any and appropriate coating method can be adopted. For example, each layer can be formed by drying after coating. As the coating method, coating methods such as using a multifunctional coater, a die coater, a gravure coater, an applicator, etc. can be cited. As the drying method, for example, natural drying, heat drying, etc. can be cited. The heating temperature during heat drying can be set to any and appropriate temperature according to the characteristics of the material to be dried.
[0115] H. Application
[0116] The adhesive tape of the present invention can be suitably used as a sheet for temporarily fixing electronic component materials when manufacturing / evaluating electronic components. In one embodiment, the adhesive tape of the present invention can be used as an adhesive tape for temporarily fixing the test body in a cold and hot shock test. In other embodiments, the adhesive tape of the present invention can be used as an adhesive tape for temporarily fixing the processed body in the resin sealing process when manufacturing a semiconductor package without a substrate. Here, the semiconductor package refers to: the form of a package of a semiconductor component that enables a single high-integration semiconductor to be surface-mounted on a printed substrate. Specifically, it refers to a wafer-level chip scale package (WLCSP), a fan-out wafer-level package (FOWLP), a fan-in wafer-level package (FIWLP), etc. In the resin sealing process of manufacturing these packages, heating for resin curing occurs and resin injection pressure is generated, but the adhesive tape needs to resist them and keep them in a specified position so that the bare chip will not move. In addition, the function of simply peeling off from the bare chip after the sealing process is required. That is, the adhesive tape disclosed in the present application can be suitably used to manufacture the aforementioned package, especially to fully exert this function in the resin sealing process. Furthermore, in other embodiments, the adhesive tape of the present invention can be used as an adhesive tape for temporarily fixing the processed body in the pattern forming process of the wiring circuit. Furthermore, in other embodiments, the adhesive tape of the present invention can be used as an adhesive tape for temporarily fixing the processed body in the electrode coating / drying process of the electronic component. Furthermore, in other embodiments, the adhesive tape of the present invention can be used as an adhesive tape for temporarily fixing the adherend so that the small-piece process and the heat treatment process of the electronic component can be carried out continuously on the same tape. Like this, the adhesive tape of the present invention can be suitably used in the process accompanied by heating.
[0117] Example
[0118] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0119] [evaluate]
[0120] (1) Initial adhesion
[0121] The adhesive tape was cut into a size of 20 mm in width and 140 mm in length. According to JIS Z 0237 (2000), a polyethylene terephthalate film (trade name "Lumirror S-10", manufactured by Toray Industries, Ltd.; thickness: 25 μm, width: 25 mm) as an adherend was pressed onto the adhesive layer by a 2 kg roller back and forth once at a temperature of 25 ° C and a humidity of 65% RH. Next, the adhesive tape with the adherend was placed in a tensile testing machine (manufactured by Shimadzu Corporation, trade name "Shimadzu Autograph AG-120 kN") with a constant temperature bath set at 25 ° C and placed for 30 minutes. Thereafter, the load when the adherend was peeled off from the adhesive tape at a peeling angle of 180 ° and a tensile speed of 300 mm / min was measured, and the maximum load at this time (the maximum value of the load after the initial peak of the measurement was removed) was obtained, and the maximum load was used as the adhesive force (N / 20 mm).
[0122] (2) Chip scattering and chip residue
[0123] (Chip scattering)
[0124] A QFN lead frame (size: 125 mm × 65 mm; the surface to which the adhesive sheet is attached is the resin surface) sealed with epoxy resin (manufactured by Hitachi Chemical Co., Ltd., trade name "CEL-9200HF9") is attached to the adhesive layer of each adhesive tape, and it is mounted and fixed on a 6-inch cutting ring, and is completely cut into chips of size 5 mm × 5 mm with the help of a cutter (cutting is performed by cutting). During this cutting, the number of chips that fly is calculated. At this time, the cutting blade used is ZH05-SD2000-N1-110-DD manufactured by DISCO. The feed speed of the cutting blade is set to 70 mm / S, and the rotation speed of the cutting blade is set to 50000 / s.
[0125] The ratio (chip scattering rate) (%) of the number of chips peeled off from the adhesive tape (chip scattering) during the cutting process is calculated as an evaluation of the cutting processability. It should be noted that when all chips are attached to the adhesive tape and not peeled off, the chip scattering rate is 0% (i.e., the chip scattering rate is 0%). The number of chips cut is set as A0, the number of chips scattered is set as A, and the chip scattering rate X is calculated according to formula (1).
[0126] X=(A / A0)×100···(1)
[0127] The smaller the chip peeling ratio (chip scattering rate), the better the chip scattering resistance is.
[0128] (Chip residue)
[0129] After the above-mentioned cutting, a program temperature regulator (hot air dryer) (manufactured by Isuzu Seisakusho, "EP-K-300") is used to perform a heat treatment at the foaming temperature for 5 minutes. After the heat treatment, the adhesive tape is turned upside down in the air (so that the chip faces downward), and the chip is peeled off by naturally falling from the adhesive tape, and the proportion of chips remaining on the sheet (chip residue) (%) is calculated. It should be noted that when all chips are peeled off and do not remain on the adhesive tape, the chip residue is 0%. Therefore, the small amount of residual chips after the heat treatment (small chip residue) means that the heat peeling property is good. The number of chips before peeling is set to B0, the number of chips remaining on the sheet after the heat peeling treatment is set to B, and the chip residue Y is calculated according to formula (2).
[0130] Y=(B / B0)×100···(2)
[0131] (3) Appearance (adhesive layer floating)
[0132] Each adhesive tape was cut into a size of 50 mm in width and 100 mm in length. After the separator was peeled off, a cutter was used to make a checkerboard-like cut (5 cuts in each of the XY directions at intervals of 5 mm) on the adhesive surface containing the heat-expandable microspheres, and the separator was attached again with a handheld roller. At this time, the adhesive layer was completely cut and the substrate was also cut.
[0133] With a 10 mm thick heat-resistant glass placed on the top plate of the heat source, a heating plate (Shamal Hot Plate "HHP-411") preheated to the foaming temperature + 20°C was used to heat the test piece (heated portion 50 mm × 50 mm) with the above-mentioned checkerboard cuts for 5 minutes, and the number of adhesive layer floatations of the sample taken out was counted.
[0134] (4) Adhesion
[0135] After the cutting in (2) above, a heating treatment is performed for 5 minutes at the foaming temperature using a program temperature regulator (hot air dryer) (manufactured by Isuzu Seisakusho, "EP-K-300"). After the heating treatment, the adhesive tape is turned upside down in the air (so that the chip faces downward), and the chip is peeled off by naturally falling from the adhesive tape, and the adhesion ratio (glue adhesion) (%) of the adhesive foreign matter on the recovered chip is confirmed by visual inspection. It should be noted that when all chips are not attached with adhesive foreign matter, the glue adhesion is 0%. Therefore, the small amount of glue adhesion (little glue adhesion) on the processed chip after the heat treatment means that the glue adhesion is good. Randomly recover 100 chips from the chips that have been heat-peeled, and set them as the denominator of formula (3) (when the number of chips that have undergone heat peeling is less than 100, this number is set to C0). The number of chips that have undergone glue adhesion is set to C, and the glue adhesion Z is calculated according to formula (3).
[0136] Z=(C / C0)×100···(3)
[0137] [Manufacturing Example 1] Preparation of Heat-Expandable Microspheres A
[0138] After adding 150 g of sodium chloride, 70 g of colloidal silica containing 20% by weight of a silica active ingredient (manufactured by Nissan Chemical Co., Ltd., trade name "SNOWTEX"), 1 g of polyvinyl pyrrolidone, and 0.5 g of a condensate of diethanolamine and adipic acid to 600 g of distilled water, the pH of the resulting mixture was adjusted to 2.8 to 3.2 to obtain an aqueous solution.
[0139] To the aqueous solution, 125 g of acrylonitrile and 120 g of methacrylic acid were added as oil-based additives to serve as shell materials, and 1 g of ethylene glycol dimethacrylate was further added as a crosslinking agent to obtain a reaction solution.
[0140] The above reaction solution was added to a pressure-resistant reaction vessel equipped with a homogenizer (manufactured by Tokushiki Kagaku Kogyo Co., Ltd., trade name "TK Homogenizer"), and further, 20 g of isopentane (boiling point: 27.7°C), 55 g of isooctane (boiling point: 99°C) and 5 g of an initiator (diisopropoxydicarbonate) as an organic solvent intentionally contained in the shell were added to the pressure-resistant reaction vessel.
[0141] The above reaction solution is added to a pressure-resistant reaction vessel equipped with a homogenizer (manufactured by Tokushiki Kagaku Kogyo Co., Ltd., trade name "TK Homogenizer"), and further, 70 g of isobutane (boiling point: -11.7°C) as an organic solvent intentionally contained in the shell and 5 g of an initiator (diisopropoxydicarbonate) are added to the pressure-resistant reaction vessel.
[0142] The homogenizer was rotated with the initial stirring condition (stirring speed: 8000rpm, stirring time: 2 minutes) of the prescribed mixture, and then the mixture was stirred at 80rpm and heated to 60°C for 24 hours. The solid component obtained by the reaction solution after the filtration reaction was placed under nitrogen gas flow, at room temperature for one week to obtain heat-expandable microspheres.
[0143] It should be noted that the gained heat-expandable microsphere utilizes the result that the trade name " SALD-2000J " made by Shimadzu Corporation is measured, and average particle diameter is 25 μm. In addition, utilize X-ray CT (ZEISS company system, Xradia520versa (measurement conditions: tube voltage 60KV, tube current 83μA, pixel size 0.20μm / pixel) as can be known: the solvent in the heat-expandable microsphere is isopentane and isooctane, relative to the weight of heat-expandable microsphere, comprises 15 weight %. In addition, utilize the result that above-mentioned X-ray CT is measured, the thickness of the shell of heat-expandable microsphere is 2.5μm.
[0144] [Manufacturing Examples 2 to 7] Heat-expandable microspheres B to K
[0145] The composition of the oil additive (acrylonitrile, methacrylic acid, methacrylonitrile, methyl methacrylate, acrylic acid) was set as described in Table 1. Heat-expandable microspheres B to K were prepared in the same manner as in Manufacturing Example 1. In addition, the average particle size of the heat-expandable microspheres was measured in the same manner as in Manufacturing Example 1. The results are shown in Table 3.
[0146] [Example 1]
[0147] (Preparation of elastic layer forming composition)
[0148] 100 parts by weight of an acrylic copolymer (a copolymer of 2-ethylhexyl acrylate (2EHA), ethyl acrylate (EA), methyl methacrylate (MMA) and 2-hydroxyethyl acrylate (HEA), 2EHA structural unit: EA structural unit: MMA structural unit: HEA structural unit = 30:70:5:5 (weight ratio)), 1 part by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L"), and toluene were mixed to prepare a composition for forming an elastic layer.
[0149] (Preparation of Adhesive Layer-Forming Composition)
[0150] An adhesive layer-forming composition was prepared by mixing 100 parts by weight of an acrylic copolymer (a copolymer of 2-ethylhexyl acrylate (2EHA), ethyl acrylate (EA), methyl methacrylate (MMA) and 2-hydroxyethyl acrylate (HEA), 2EHA structural unit: EA structural unit: MMA structural unit: HEA structural unit = 30:70:5:5 (weight ratio)), 20 parts by weight of a tackifier (manufactured by Yasuhara Chemical Co., Ltd., trade name "Mighty Ace G125"), 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L"), 30 parts by weight of heat-expandable microspheres A, and toluene.
[0151] (Manufacturing of Adhesive Tape)
[0152] The elastic layer-forming composition was applied onto a PET film (manufactured by Toray Industries, trade name "Lumirror S10", thickness: 100 μm) as a substrate and dried to form an elastic layer (thickness: 15 μm) on the substrate.
[0153] The pressure-sensitive adhesive layer-forming composition was applied onto a polyethylene terephthalate film (MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) with a silicone release agent-treated surface and dried to form a pressure-sensitive adhesive layer (35 μm) on the polyethylene terephthalate film.
[0154] The adhesive layer formed on the polyethylene terephthalate film was transferred to the elastic layer to obtain an adhesive tape having a substrate, an elastic layer and an adhesive layer in this order. The obtained adhesive tape was subjected to the above evaluations (1) to (4). The results are shown in Table 3.
[0155] [Examples 2 to 14, Comparative Examples 1 to 2]
[0156] The same procedure as in Example 1 was performed except that the compositions of the elastic layer-forming composition (base polymer composition, crosslinking amount) and the adhesive layer-forming composition (base polymer composition, crosslinking agent type, crosslinking amount, heat-expandable microsphere type) were set to the compositions shown in Table 1 or Table 2 to obtain an adhesive tape. The obtained adhesive tape was subjected to the above-mentioned evaluations (1) to (4). The results are shown in Table 3. It should be noted that in Table 1 or Table 2, "crosslinking agent TETRAD C" is an epoxy crosslinking agent (trade name "TETRAD C") manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0157] [Example 15]
[0158] In the same manner as in Example 1, a composition for forming an adhesive layer was prepared.
[0159] The above adhesive layer forming composition was applied to a PET film (manufactured by Toray Industries, trade name "Lumirror ES-10", thickness: 100 μm) as a substrate and dried to form an adhesive layer on the substrate to obtain an adhesive tape. The obtained adhesive tape was subjected to the above evaluations (1) to (4). The results are shown in Table 3.
[0160] [Example 16]
[0161] In the same manner as in Example 1, an elastic layer-forming composition and an adhesive layer-forming composition were prepared.
[0162] Furthermore, 100 parts by weight of an acrylic copolymer (a copolymer of 2-ethylhexyl acrylate (2EHA), ethyl acrylate (EA), methyl methacrylate (MMA) and 2-hydroxyethyl acrylate (HEA), 2EHA structural unit: EA structural unit: MMA structural unit: HEA structural unit = 30:70:5:5 (weight ratio)), 10 parts by weight of a tackifier (manufactured by Yasuhara Chemical Co., Ltd., trade name "Mighty Ace G125"), 3 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATEL") and toluene were mixed to prepare another composition for forming an adhesive layer.
[0163] The elastic layer-forming composition was applied onto a PET film (manufactured by Toray Industries, trade name "Lumirror S10", thickness: 100 μm) as a substrate and dried to form an elastic layer (thickness: 15 μm) on the substrate.
[0164] The pressure-sensitive adhesive layer-forming composition was applied onto a polyethylene terephthalate film (MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) with a silicone release agent-treated surface and dried to form a pressure-sensitive adhesive layer (35 μm) on the polyethylene terephthalate film.
[0165] Separately, the above-mentioned additional adhesive layer-forming composition was applied onto a polyethylene terephthalate film (MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) with a silicone release agent-treated surface and dried to form another adhesive layer (10 μm) on the polyethylene terephthalate film.
[0166] The adhesive layer formed on the polyethylene terephthalate film is transferred to the elastic layer, and another adhesive layer is transferred to the surface of the substrate on which the elastic layer is not formed, thereby obtaining an adhesive tape having another adhesive layer, a substrate, an elastic layer and an adhesive layer in this order.
[0167] The obtained pressure-sensitive adhesive tape was subjected to the above-mentioned evaluations (1) to (4). The results are shown in Table 3.
[0168] [Example 17]
[0169] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that a PI film (manufactured by Toray Industries, Inc., trade name "Lumirror S10", thickness: 100 μm) was used instead of the PET film (manufactured by Toray Industries, Inc., trade name "Lumirror S10", thickness: 100 μm) as the substrate. The pressure-sensitive adhesive tape was subjected to the above-mentioned evaluations (1) to (4). The results are shown in Table 3.
[0170] [Example 18]
[0171] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 17 except that the pressure-sensitive adhesive tape was used instead of the pressure-sensitive adhesive tape A prepared in Preparation Example 1. The pressure-sensitive adhesive tape was subjected to the above-mentioned evaluations (1) to (4). The results are shown in Table 3.
[0172] [Comparative Example 3]
[0173] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 15 except that the heat-expandable microspheres K prepared in Preparation Example 11 were used instead of the heat-expandable microspheres A prepared in Preparation Example 1. The pressure-sensitive adhesive tape was subjected to the above-mentioned evaluations (1) to (4). The results are shown in Table 3.
[0174] [Table 1]
[0175]
[0176] [Table 2]
[0177]
[0178] ※ Example 16 has an additional adhesive layer
[0179] [Table 3]
[0180]
[0181] Description of Reference Numerals
[0182] 10 Adhesive layer
[0183] 20 Substrate
[0184] 100 Adhesive tape
Claims
1. An adhesive tape comprising a substrate and an adhesive layer disposed on at least one side of the substrate, The adhesive layer comprises heat-expandable microspheres and an adhesive. The heat-expandable microspheres are composed of a shell and a volatile substance contained in the shell. The resin constituting the shell contains a structural unit having a carboxyl group, The content ratio of the structural unit having a carboxyl group is 49 parts by weight to 97 parts by weight relative to 100 parts by weight of the resin, The volatile substance is an organic solvent, The difference (Tg-bp) between the glass transition temperature (Tg) of the resin constituting the shell and the boiling point (bp) of the organic solvent is 50° C. to 150° C., The adhesive comprises a base polymer having OH groups, The acid value of the base polymer is 0 to 100, The substrate comprises a resin sheet, The resin constituting the resin sheet is polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, polyamide, wholly aromatic polyamide, polyimide, polyvinyl chloride, polyphenylene sulfide, fluorine resin or polyetheretherketone, The pressure-sensitive adhesive tape further includes an elastic layer.
2. The adhesive tape according to claim 1, wherein The glass transition temperature (Tg) of the resin constituting the shell is 120° C. or higher.
3. The adhesive tape according to claim 1 or 2, wherein The adhesive is an acrylic adhesive.
4. The adhesive tape according to claim 1 or 2, wherein The adhesive includes an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent.
5. The adhesive tape according to claim 1 or 2, wherein At an ambient temperature of 25° C., when the adhesive surface of the adhesive tape is attached to a polyethylene terephthalate film, the initial adhesive force a is 1.5 N / 20 mm to 20 N / 20 mm.
6. The adhesive tape according to claim 1 or 2, wherein The adhesive force b when the adhesive surface of the adhesive tape heated to 130°C and then cooled to 25°C is attached to a polyethylene terephthalate film is 50% or more of the initial adhesive force a when the adhesive surface of the adhesive tape is attached to a polyethylene terephthalate film at an ambient temperature of 25°C.
7. The adhesive tape according to claim 1 or 2, wherein The adhesive force c of the adhesive surface of the adhesive tape after two cycles of heating to 130°C and then cooling to 25°C when attached to the polyethylene terephthalate film is 50% or more of the initial adhesive force a when the adhesive surface of the adhesive tape is attached to the polyethylene terephthalate film at an ambient temperature of 25°C.
8. The adhesive tape according to claim 1 or 2, wherein The adhesive layer is provided on both sides of the substrate.
9. The adhesive tape according to claim 1 or 2, wherein The adhesive layer is provided on one side of the substrate, and another adhesive layer is provided on the other side of the substrate.
Citation Information
Patent Citations
Thermally peeling type adhesive sheet
JP2001131507A
Heat-expansive and repeelable acrylic pressure-sensitive adhesive tape or sheet
CN102405268A
Adhesive tape
CN108504298A
Microsphere, thermally foamable resin composition, foam molded body and manufacturing method for same
CN108884376A
Pressure sensitive adhesive sheet
JP2015168711A